Successful treatment of prediabetes in clinical practice using physiological assessment (STOP DIABETES). Issue 10 (October 2018) - Armato, John P; DeFronzo, Ralph A; Abdul-Ghani, Muhammad; Ruby, Ron J
Summary: Background: Of the 84 million American adults with prediabetes, over 5 to 7 years, about 28 million progress to type 2 diabetes. We aimed to assess whether a real-world, pathophysiology-based, therapeutic approach could prevent development of type 2 diabetes in high-risk individuals. Methods: We did a retrospective observational study of people at increased risk of type 2 diabetes from a community practice in southern California, USA. Participants had an oral glucose tolerance test and were assigned a risk stratification on the basis of presence and severity of insulin resistance, impaired β-cell function, and glycaemia (ie, 1-h plasma glucose concentration of more than 8·6 mmol/L during an oral glucose tolerance test). Treatment was recommended on the basis of risk: metformin, pioglitazone, glucagon-like peptide-1 (GLP-1) receptor agonist, and lifestyle therapy for participants at high risk of diabetes, and metformin, pioglitazone, and lifestyle therapy for those at intermediate risk. Individuals who refused pharmacological therapy were assigned to lifestyle therapy only. Participants were followed up every 6 months and oral glucose tolerance tests were repeated at 6 months and subsequently every 2 years or sooner. The primary outcome of our analysis was incidence of type 2 diabetes according to the American Diabetes Association criteria, within the study period (2009–16). This study is registered withClinicalTrials.gov, numberNCT03308773 . Findings: Between Jan 1, 2009 and Dec 31, 2016, we assessed 1769 people at increased risk of diabetes, of which 747 (42%) were identified at high or intermediate risk and were recommended pharmacological treatment. Of 422 participants analysed, 28 (7%) progressed to type 2 diabetes (seven [5%] of 141 participants who received metformin, pioglitazone, and lifestyle therapy, none [0%] of 81 who received metformin, pioglitazone, GLP-1 receptor agonist, and lifestyle therapy, and 21 [11%] of 200 who received lifestyle therapy only) after mean follow-up of 32·09 months (SEM 1·24). Compared with participants who received lifestyle therapy only, the adjusted hazard ratio for progression to type 2 diabetes was 0·29 (95% CI 0·11–0·78, p=0·0009) in participants who received metformin and pioglitazone, and 0·12 (95% CI 0·02–0·94, p=0·04) in participants who received metformin, pioglitazone, and GLP-1 receptor agonist. Improved β-cell function was the strongest predictor of type 2 diabetes prevention. Interpretation: Progression to type 2 diabetes in people at high risk of diabetes can be markedly reduced with interventions designed to correct underlying pathophysiological disturbances (ie, impaired insulin secretion and resistance) in a real-world setting. Funding: None.